2006
DOI: 10.1089/fpd.2006.3.88
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Epidemiologic Subtyping of Shiga Toxin–ProducingEscherichia coliStrains Isolated from Hemolytic Uremic Syndrome and Diarrhea Cases in Argentina

Abstract: Argentina has a high incidence of hemolytic uremic syndrome (HUS); 12.2 cases per 100,000 children younger than 5 years old were reported in 2002. Shiga toxin (Stx)-producing Escherichia coli (STEC) is the primary etiologic agent of HUS, and STEC O157 is the predominant serogroup isolated. The main objective of the present work was to establish the phenotypic and genotypic characteristics of the STEC strains in general isolated from Argentine children during a prospective study and the clonal relatedness of ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(121 citation statements)
references
References 40 publications
6
109
1
5
Order By: Relevance
“…Different serotypes determined from the diarrheic isolates were mostly the classical non-O157 enterohemorrhagic E. coli (EHEC) serotypes such as O26:H11, O111:H2, O113:H7, O103:H2, and O145:H28 [19]. From healthy persons, only two serotypes were identified (O26:H11 and O111:H2); this finding is in agreement with many previous studies which verified that O26 is considered one of the most clinically serotypes that could be isolated from both diarrheic and healthy persons [20,21].…”
Section: Discussionsupporting
confidence: 90%
“…Different serotypes determined from the diarrheic isolates were mostly the classical non-O157 enterohemorrhagic E. coli (EHEC) serotypes such as O26:H11, O111:H2, O113:H7, O103:H2, and O145:H28 [19]. From healthy persons, only two serotypes were identified (O26:H11 and O111:H2); this finding is in agreement with many previous studies which verified that O26 is considered one of the most clinically serotypes that could be isolated from both diarrheic and healthy persons [20,21].…”
Section: Discussionsupporting
confidence: 90%
“…A more recent Mexican case-control study reported that in more than 50% of cases of diarrhoea there was more than one pathogen implicated, including any combination of E. histolytica, Salmonella, or E. coli pathogens [33]. Case-control studies reported from Argentina have concentrated more on STEC, as this country has a high incidence of hemolytic uremic syndrome associated with O157:H7 and non-O157:H7 STEC strains [34].…”
Section: Discussionmentioning
confidence: 99%
“…Most compellingly, E. coli O157:H7 is the STEC/VTEC that remains to this day the near-exclusive cause of postdiarrheal HUS (8,12,16,21,(43)(44)(45)(46)(47)(48)(49). This serotype is also the one most strongly associated with outbreaks (though most infections are sporadic).…”
Section: Distinction Between Stec/vtec Belonging To Serotype O157:h7 mentioning
confidence: 99%